1999
DOI: 10.1111/j.1532-5415.1999.tb01556.x
|View full text |Cite
|
Sign up to set email alerts
|

Home Visits by an Occupational Therapist for Assessment and Modification of Environmental Hazards: A Randomized Trial of Falls Prevention

Abstract: Home visits by occupational therapists can prevent falls among older people who are at increased risk of falling. However, the effect may not be caused by home modifications alone. Home visits by occupational therapists may also lead to changes in behavior that enable older people to live more safely in both the home and the external environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
325
0
22

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(353 citation statements)
references
References 21 publications
6
325
0
22
Order By: Relevance
“…For example, stairs intervene as a barrier for walker users, and ramps are a facilitator for wheelchair users. 30 Some clinical trials have shown that the removal of architectural barriers, such as stairs, slowed the dependence on ADLs 31 and decreased the incidence of falls 32,33 and the costs of certain health and social services. 31 Some limitations should be mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…For example, stairs intervene as a barrier for walker users, and ramps are a facilitator for wheelchair users. 30 Some clinical trials have shown that the removal of architectural barriers, such as stairs, slowed the dependence on ADLs 31 and decreased the incidence of falls 32,33 and the costs of certain health and social services. 31 Some limitations should be mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational therapy expertise is valued for its fall prevention interventions such as assertiveness training, exercise programmes, home evaluations and modification, functional assessments, assistive device training, and risk-reduction education (Caldeira & Reitz, 2009). In addition, exercise and home visits performed by occupational therapists will facilitate self-reflection and improve awareness of the risk factors of the environment surrounding the patient in order to prevent future falls (Caldeira & Reitz, 2009;Cumming et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Sie können in monofaktorielle Trainingsprogramme (Cumming et al, 1999;Steultjens, Dekker, Bouter, Jellema, & Bakker, 2004;Clemson, Mackenzie, Ballinger, Close, & Cumming, 2008;Costello, & Edelstein, 2008;Sherrington et al, 2008;Davis et al, 2010;Sherrington, Tiedemann, Fairhall, Close, & Lord, 2011;Leland, Elliott, O'Malley, & Murphy, 2012) und in multifaktorielle Trainingsprogramme (Steultjens et al, 2004;Costello, & Edelstein, 2008;Peterson, & Clemson, 2008, Sherrington et al, 2008Davis et al, 2010;Sherrington et al, 2011;Leland, et al, 2012) eingeteilt werden. Beide Formen können entweder als Gruppen-oder Einzeltraining in der eigenen Häuslichkeit angeboten werden (Costello, & Edelstein, 2008 (Steultjens et al, 2004;Costello, & Edelstein, 2008;Sherrington et al, 2008;Davis et al, 2010;Sherrington et al, 2011), c) Anleitung, Beratung und Edukation von Angehörigen (Steultjens et al, 2004) sowie d) additiv-begleitendes Training kognitiver Funktionen (Steultjens et al, 2004).…”
Section: Wirkweise Körperlicher Trainingsprogrammeunclassified
“…Monofaktorielle wie auch multifaktorielle Programme sind maßgeschneidert und enthalten vornehmlich diejenigen Trainingselemente, die zuvor mittels Assessments identifiziert wurden. Gemäß der Meta-Analyse von Sherrington et al (2011) (Cumming et al, 1999;Pardessus et al, 2002;Steultjens et al, 2004;Costello, & Edelstein, 2008;Clemson et al, 2008;Davis et al, 2010;Pighills, Torgerson, Sheldon, Drummond, & Bland, 2011;Leland et al, 2012;Ballinger, & Brooks, 2013 (Peterson, & Clemson, 2008). Der Durchführung von Wohnraumanpassungen durch Ergotherapeuten/-innen wird hohes Potenzial zugeschrieben (Costello, & Edelstein, 2008), da Ergotherapeuten/-innen über die notwendigen fachlichen Qualifikationen verfügen, insbesondere bei der Durchführung von Wohnraumassessments und -anpassungen (Steinmetz, & Hobson, 1994;Cumming et al, 1999;Lampiasi, & Jacobs, 2010).…”
Section: Wirkweise Körperlicher Trainingsprogrammeunclassified
See 1 more Smart Citation